Exploring end of life priorities in Saudi males: usefulness of Q-methodology. Issue 1 (December 2015) - Hammami, Muhammad; Al Gaai, Eman; Hammami, Safa; Attala, Sahar
Abstract Background Quality end-of-life care depends on understanding patients' end-of-life choices. Individuals and cultures may hold end-of-life priorities at different hierarchy. Forced ranking rather than independent rating, and by-person factor analysis rather than averaging may reveal otherwise masked typologies. Methods We explored Saudi males' forced-ranked, end-of-life priorities and dis-priorities. Respondents (n  = 120) rank-ordered 47 opinion statements on end-of-life care following a 9-category symmetrical distribution. Statements' scores were analyzed by averaging analysis and factor analysis (Q-methodology). Results Respondents' mean age was 32.1 years (range, 18–65); 52 % reported average religiosity, 88 and 83 % ≥ very good health and life-quality, respectively, and 100 % ≥ high school education. Averaging analysis revealed that the extreme five end-of-life priorities were to, be at peace with God, be able to say the statement of faith, maintain dignity, resolve conflicts, and have religious death rituals respected, respectively. The extreme five dis-priorities were to, die in the hospital, not receive intensive care if in coma, die at peak of life, be informed about impending death by family/friends rather than doctor, and keep medical status confidential from family/friends, respectively. Q-methodology classified 67 % of respondents into five highly transcendent opinion types. Type-I (rituals-averse, family-caring, monitoring-coping, life-quality-concerned) and Type-V (rituals-apt, family-centered, neutral-coping, life-quantity-concerned) reported the lowest and highest religiosity, respectively. Type-II (rituals-apt, family-dependent, monitoring-coping, life-quantity-concerned) and Type-III (rituals-silent, self/family-neutral, avoidance-coping, life-quality & quantity-concerned) reported the best and worst life-quality, respectively. Type-I respondents were the oldest with the lowest general health, in contrast to Type-IV (rituals-apt, self-centered, monitoring-coping, life-quality/quantity-neutral). Of the extreme 14 priorities/dis-priorities for the five types, 29, 14, 14, 50, and 36 %, respectively, were not among the extreme 20 priorities/dis-priorities identified by averaging analysis for the entire cohort. Conclusions 1) Transcendence was the extreme end-of-life priority, and dying in the hospital was the extreme dis-priority. 2) Quality of life was conceptualized differently with less emphasize on its physiological aspects. 3) Disclosure of terminal illness to family/close friends was preferred as long it is through the patient. 4) Q-methodology identified five types of constellations of end-of-life priorities and dis-priorities that may be related to respondents' demographics and are partially masked by averaging analysis.